Identification of dimensions in Organizational Safety Climate and relationship with safety behavior - Yi, Jonghan; Lee, JongGoo; Seok, DongHeon (Korean Journal of Industrial and Organizational Psychology, 2011)
The purposes of this study were 1) to identify the dimensions of organizational safety climate and 2) to examine how these dimensions were related to safety climate and safety behavior in organization. The present study proposed 10 dimensions of safety climate (Management's commitment; Effectiveness of safety communication; Safety rules and procedures; Supportive environment; Supervisory environment; Worker's involvement; Appraisal of physical work environment and work hazards; Work pressure; Competence; Safety training) based on Mohamed(2002)'s and Zohar(1980)'s study. Questionnaire was administered to 210 workers in a shipbuilding company. The results of the confirmatory factor analysis showed that these 10 dimensions could be the valid factors of safety climate. The results of the multiple regression analysis which utilized safety climate as a criterion revealed that 4 dimensions were significant predictors(Appraisal of physical work environment and work hazards, Safety rules and procedures, Worker's involvement, Management's commitment). The same multiple regression analysis which used safety behavior as a criterion showed that 5 dimensions were significant predictors(Competence, Management's commitment, Safety rules and procedures, Worker's involvement, Supportive environment). Limitations of the study and implications for future research were discussed.